Mathematical methods and tools for increasing the efficiency of health care organizations - V. A. Titov; S. N. Tsyganov (Открытое образование (Москва))
Activities of medical organizations assume the processing and analyzing large volumes of information to solve diagnostic and treatment tasks and management problems. An effective solution, related to collecting, processing and storing of the medical information, practical managing of information flows, short-term and long-term planning, economical, statistical and financial analyzing requires the use of special tools.The purpose of this research is to determine the mathematical methods and to develop the tools for analyzing the efficiency of medical organization. The tools’ use will improve not only the efficiency of a single organization, but also the quality of the patient care in general.The material of this research is primary medical information, stored on Microsoft SQL Server. Information processing is carried out on the basis of economic and mathematical methods and methods of mathematical statistics and decision theory. It is proposed to use such tools as automated control system of medical services’ cost management and health care economist’s workstation. Further processing is carried out in Microsoft Excel using pivot tables and macros. The statistical package Statgraphics is used for analyzing the efficiency of the group of medical organizations. This article has considered three components of efficiency – clinical, organizational and economic. Cost-effectiveness analysis was conducted on the basis of economical and mathematical methods and methods of mathematical statistics and decision theory in areas of cost analysis and evaluation of the resources use. The mechanism of classifying the efficiency of the activity of medical organizations on the structure of the cost of services was offered. The use of the research results allowed to develop the software that has a practical experience of successful applying in a number of medical organizations. The feasibility of the tools ’use to improve the efficiency of health care organizations was shown.The expected effects of the introduction of tools to the work of medical organizations are the following: improving the efficiency and quality of health care by providing high-quality health information, reducing he time on paperwork, accumulating information in a structured and formalized form suitable for the further use. The economist’s workstation helps users to standardize workflows and information exchange, allows to analyze functioning capacity of the medical organization, doctors, offices, and receive a summary of the rendered medical services during the period. The automated control system of medical services cost management allows users to control the cost of services on the basis of the calculation of economically justified costs and labor resources.